2019
DOI: 10.1186/s12913-018-3862-7
|View full text |Cite|
|
Sign up to set email alerts
|

Healthcare professionals’ perspectives on working conditions, leadership, and safety climate: a cross-sectional study

Abstract: BackgroundPromoting patient and occupational safety are two key challenges for hospitals. When aiming to improve these two outcomes synergistically, psychosocial working conditions, leadership by hospital management and supervisors, and perceptions of patient and occupational safety climate have to be considered. Recent studies have shown that these key topics are interrelated and form a critical foundation for promoting patient and occupational safety in hospitals. So far, these topics have mainly been studie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
69
1
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1
1

Relationship

2
8

Authors

Journals

citations
Cited by 85 publications
(84 citation statements)
references
References 67 publications
5
69
1
3
Order By: Relevance
“…Previous work, for example, has shown that physicians report higher levels of PSC when there is good teamwork across units and a unit-level management that promotes PSC 31. Nursing staff, by contrast, are more likely to report higher levels of PSC safety when they feel that there is enough staff in the unit 31–33. In addition to these concerns, the psychometric properties of PSC instruments may be affected by other factors such as national culture 34.…”
Section: Introductionmentioning
confidence: 99%
“…Previous work, for example, has shown that physicians report higher levels of PSC when there is good teamwork across units and a unit-level management that promotes PSC 31. Nursing staff, by contrast, are more likely to report higher levels of PSC safety when they feel that there is enough staff in the unit 31–33. In addition to these concerns, the psychometric properties of PSC instruments may be affected by other factors such as national culture 34.…”
Section: Introductionmentioning
confidence: 99%
“…Some studies have suggested that working environment deterioration of healthcare workers is associated with an increase in the number of event reports [11,12]; however, few studies have examined the influence of working hours, the number of night shifts, and the number of days off on patient safety culture. Working environment associated with each profession may affect patient safety culture differently because each profession has different working environment characteristics [13][14][15].…”
Section: Introductionmentioning
confidence: 99%
“…The instrument development process described here was part of the larger research project ‘Working conditions, safety culture and patient safety in hospitals—what predicts the safety of the medication process?’ (WorkSafeMed) that examined the associations between frontline staff perceptions of working conditions, patient safety, occupational safety climate and patient safety outcomes. WorkSafeMed was a cross-sectional study conducted between 2014 and 2017 in two German university hospitals 37…”
Section: Methodsmentioning
confidence: 99%